Outcomes of surgical versus transcatheter aortic valve replacement in nonagenarians- a systematic review and meta-analysis - Azka Latif; Muhammad Junaid Ahsan; Noman Lateef; Vikas Kapoor; Mohsin Mansoor Mirza; Faiz Anwer; Michael Del Core; Arun Kanmantha Reddy (Greater Baltimore Medical Center, 2021)
Introduction: Since the approval of transcatheter aortic valve replacement (TAVR), nonagenarian group patients are being increasingly considered for TAVR. Therefore, we compared the clinical outcomes of surgical aortic valve replacement (SAVR) vs TAVR in nonagenarians with severe aortic stenosis. Methods: A literature search was performed using MEDLINE, Embase, Web of Science, Cochrane, and Clinicaltrials.gov for studies reporting the comparative outcomes of TAVR versus SAVR in nonagenarians. The primary endpoint was short-term mortality. Secondary endpoints were post-operative incidences of stroke or transient ischemic attack (TIA), vascular complications, acute kidney injury (AKI), transfusion requirement, and length of hospital stay. Results: Four retrospective studies qualified for inclusion with a total of 8,389 patients (TAVR = 3,112, SAVR = 5,277). Short-term mortality was similar between the two groups [RR = 0.91 (95% CI: 0.76-1.10), p = 0.318]. The average length of hospital stay was shorter by 3 days in the TAVR group (p = 0.037). TAVR was associated with a significantly lower risk of AKI [RR = 0.72 (95% CI: 0.62-0.83), p < 0.001] and a lower risk of transfusion [RR = 0.71 (95% CI: 0.62-0.81), p < 0.001]. There was no difference in risk of stroke/TIA[RR = 1.01 (95% CI: 0.70-1.45), p = 0.957]. The risk of vascular complications was significantly higher in the TAVR group [RR = 3.39 (95% CI: 2.65-4.333), p < 0.001]. Conclusion: In this high-risk population, TAVR compared to SAVR has similar short-term mortality benefit but has lower risks of perioperative complications and a higher number of patients being discharged to home.